Assessing EFL Students' Writing Skills: Moving Beyond the Traditional Examination Format Case of First Year LMDStudents of English language atMohamed-CherifMessaadia University of Souk-Ahras. - SELATNIA Abir (My University, 2024)
ABSTRACT This study explores EFL teachers’ assessment practices during their writing sessions with first year LMD students in the department of English at Mohamed CherifMessadia University of Souk Ahras. It aims to investigate teachers’ awareness and actual use of alternative assessment formats beyond the traditional ones, as well as, the impact of these alternative formats on EFL learners’ writing skills development. Our exploratory research employs a mixed-methods design, combining quantitative data from teachers’ questionnaires with qualitative insights from classroom observation. The obtained findings highlight that the traditional examination format falls short in assessing EFL students' writing skills as it primarily focuses on surface-level aspects such as grammar and vocabulary, neglecting the holistic evaluation of students' critical thinking, creativity, organization, and coherence in writing. Also, alternative approaches, such as portfolio assessment, process-based assessment, and the integration of authentic writing tasks, can provide a more comprehensive and authentic evaluation of EFL students' writing skills ------------------- ملخص تستكشف هذه الدراسة ممارسات تقييم معلمي اللغة الإنجليزية كلغة أجنبية أثناء جلسات الكتابة مع طلاب السنة الأولى في قسم اللغة الإنجليزية في جامعة محمد شريف مسعدية بسوق أهراس. تهدف الدراسة إلى التحقيق في وعي المعلمين واستخدامهم الفعلي لصيغ التقييم البديلة بعيدًا عن الصيغ التقييمية التقليدية، وكذلك تأثير هذه الصيغ البديلة على تطوير مهارات الكتابة لدى متعلمي اللغة الإنجليزية كلغة أجنبية. تعتمد الدراسة البحثية التكشفية التي نقوم بها تصميمًا مختلطًا، حيث تجمع بين البيانات الكمية من استبيانات المعلمين والنظرات الكيفية النوعية من مراقبة الفصول الدراسية. تسلط النتائج التي تم الحصول عليها الضوء على أن الصيغة التقييمية التقليدية تفتقر في تقييم مهارات الكتابة لدى متعلمي اللغة الإنجليزية كلغة أجنبية، حيث تركز بشكل أساسي على جوانب سطحية مثل القواعد والمفردات، متجاهلة التقييم الشامل للتفكير النقدي والإبداع والتنظيم والترابط في الكتابة. أيضًا، تعتبر النهج البديلة مثل تقييم الملف الشخصي وتقييم العملية ودمج مهام الكتابة الأصيلة، يمكن أن توفر تقييمًا أكثر شمولية وأصالة لمهارات الكتابة لدى متعلمي اللغة الإنجليزية كلغة أجنبية --------------- RÉSUMÉ Cette étude explore les pratiques d'évaluation des enseignants d'anglais langue étrangère (ALE) lors de leurs séances d'écriture avec les étudiants de première année LMD du département d'anglais de l'Université Mohamed Cherif Messadia de Souk Ahras. Elle vise à examiner la prise de conscience et l'utilisation réelle par les enseignants de formats d'évaluation alternatifs, au-delà des formats traditionnels, ainsi que l'impact de ces formats alternatifs sur le développement des compétences en écriture des apprenants d'anglais langue étrangère. Notre recherche exploratoire utilise une conception mixte, combinant des données quantitatives issues de questionnaires d'enseignants avec des informations qualitatives provenant de l'observation en classe. Les résultats obtenus mettent en évidence les limites du format d'examen traditionnel dans l'évaluation des compétences en écriture des apprenants d'anglais langue étrangère, car il se concentre principalement sur des aspects de surface tels que la grammaire et le vocabulaire, négligeant l'évaluation holistique de la pensée critique, de la créativité, de l'organisation et de la cohérence des étudiants dans leur écriture. De plus, des approches alternatives telles que l'évaluation par portfolio, l'évaluation basée sur le processus et l'intégration de tâches d'écriture authentiques peuvent fournir une évaluation plus complète et authentique des compétences en écriture des apprenants d'anglais langue étrangère.